On Derandomizing Local Distributed Algorithms - Ghaffari, Mohsen; Harris, David G.; Kuhn, Fabian (2018 IEEE 59th Annual Symposium on Foundations of Computer Science (FOCS), 2018)
The gap between the known randomized and deterministic local distributed algorithms underlies arguably the most fundamental and central open question in distributed graph algorithms. In this paper, we combine the method of conditional expectation with network decompositions to obtain a generic and clean recipe for derandomizing LOCAL algorithms. This leads to significant improvements on a number of problems, in cases resolving known open problems. Two main results are: - An improved deterministic distributed algorithm for hypergraph maximal matching, improving on Fischer, Ghaffari, and Kuhn [FOCS '17]. This yields improved algorithms for edge-coloring, maximum matching approximation, and low out-degree edge orientation. The last result gives the first positive resolution in the Open Problem 11.10 in the book of Barenboim and Elkin. - Improved randomized and deterministic distributed algorithms for the Lovász Local Lemma, which get closer to a conjecture of Chang and Pettie [FOCS '17].